Impact assessment of energy‐efficient lighting in patients with lupus erythematosus: a pilot study3. (March 2014) - Fenton, L.; Dawe, R.; Ibbotson, S.; Ferguson, J.; Silburn, S.; Moseley, H.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Patients with lupus erythematosus (LE) can have abnormal cutaneous response to ultraviolet (UV) radiation. Compact fluorescent lamps (CFLs) emit UV that can exacerbate certain photodermatoses. UV‐induced cutaneous response may lead to general disease progression including systemic activity. What does this study add? Skin erythema is induced by repeated CFL exposure in healthy individuals and those with LE. CFL‐induced erythema is more persistent in individuals with LE. Light‐emitting diodes offer a safe alternative light source for individuals with LE, without the risk of UV.